Pengaruh Leverage Dan Profitabilitas Terhadap Transfer Pricing Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019 – 2023 - Enyvia Natania Siagian; Hasbiana Dalimunthe (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2024)
The aim of this research is to examine the impact of leverage and profitability on transfer pricing through various food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2023. Researchers used quantitative techniques in this research using secondary data. Purposive sampling is a technique used by researchers in the sampling stage. The analytical method used is multiple linear regression on 11 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the 2019 - 2023 period. The research results obtained show that leverage partially has a negative and unidirectional influence on transfer pricing, while profitability has a positive and significant influence on transfer pricing. Simultaneously, leverage and profitability have a good or positive and significant impact on transfer pricing